Analisis Kelayakan Ekonomi dan Kesiapan SDM SPKLU 22 kW untuk Mendukung Transisi Energi - Sulastri, Sulastri (Journal of Authentic Research, 2026)
Transisi energi global mendorong elektrifikasi sektor transportasi melalui penggunaan kendaraan listrik sebagai upaya untuk mengurangi emisi karbon dan ketergantungan terhadap bahan bakar fosil. Keberhasilan implementasi kendaraan listrik sangat dipengaruhi oleh ketersediaan infrastruktur pengisian daya, khususnya Stasiun Pengisian Kendaraan Listrik Umum (SPKLU). Selain berperan dalam mendukung transisi energi, SPKLU juga memiliki potensi ekonomi sebagai unit bisnis berbasis penjualan energi listrik. Penelitian ini bertujuan untuk menganalisis kelayakan ekonomi operasional SPKLU berkapasitas 22 kW, mengevaluasi peran sistem pengukuran energi berbasis kWh meter dalam model bisnis pengisian kendaraan listrik, serta mengkaji kesiapan sumber daya manusia (SDM) dalam pengelolaan fasilitas pengisian kendaraan listrik. Penelitian menggunakan pendekatan analisis teknis–ekonomi dengan asumsi operasional tertentu, meliputi kapasitas charger 22 kW, tingkat utilisasi rata-rata 60%, waktu operasi 8 jam per hari selama 300 hari per tahun, serta efisiensi fasilitas sebesar 95%. Analisis kelayakan ekonomi dilakukan menggunakan indikator Return on Investment (ROI) dan Break Even Point (BEP). Hasil penelitian menunjukkan bahwa SPKLU mampu menyalurkan energi listrik sebesar 31.680 kWh per tahun dengan pendapatan tahunan sebesar Rp95.040.000 dan laba bersih sekitar Rp35.019.500 per tahun. Dengan investasi awal sebesar Rp200.000.000, periode pengembalian investasi diperkirakan sekitar 5,7 tahun dengan nilai ROI sebesar 17,5% per tahun. Temuan ini menunjukkan bahwa SPKLU berpotensi layak secara ekonomi pada tingkat utilisasi moderat. Selain itu, sistem pengukuran energi berbasis kWh meter berperan penting dalam menjamin transparansi transaksi energi, meningkatkan efisiensi operasional, serta mendukung analisis kelayakan bisnis. Pengembangan SPKLU juga memerlukan dukungan sumber daya manusia yang memiliki kompetensi teknis dalam pengoperasian dan pengelolaan sistem pengisian kendaraan listrik. The global energy transition has accelerated the electrification of the transportation sector through the adoption of electric vehicles as an effort to reduce carbon emissions and dependence on fossil fuels. The successful implementation of electric vehicles is highly dependent on the availability of charging infrastructure, particularly Public Electric Vehicle Charging Stations (SPKLU). In addition to supporting the energy transition, SPKLU also has economic potential as a business unit based on electricity sales. This study aims to analyze the economic feasibility of operating a 22 kW SPKLU, evaluate the role of a kWh meter–based energy measurement system in the electric vehicle charging business model, and examine the readiness of human resources in managing charging station operations. The study employs a techno-economic analysis approach using several operational assumptions, including a 22 kW charger capacity, an average utilization rate of 60%, operating time of 8 hours per day for 300 days per year, and facility efficiency of 95%. The economic feasibility analysis is conducted using Return on Investment (ROI) and Break Even Point (BEP) indicators. The results show that the charging station can deliver approximately 31,680 kWh of electricity annually, generating annual revenue of IDR 95,040,000 and a net profit of around IDR 35,019,500 per year. With an initial investment of IDR 200,000,000, the investment payback period is estimated at approximately 5.7 years, with an ROI of about 17.5% per year. These findings indicate that SPKLU has promising economic feasibility at a moderate utilization level. Furthermore, the kWh meter–based energy measurement system plays a crucial role in ensuring transaction transparency, improving operational efficiency, and supporting business feasibility analysis. The development of SPKLU also requires competent human resources with technical expertise in operating and managing electric vehicle charging systems.Abstract is written in italics (Italic) for English abstracts of 150-250 words with a font size of 9  pt and the typeface is Book Antiqua Style and the spacing between lines is one space. If the article is in Indonesian, the abstract must be written in good and correct Indonesian and English. If the article is in English, then the abstract must be written in English only. The Abstract section must contain the objectives, the core of the problem to be raised, the method of solving it, and the results of scientific findings obtained and conclusions. Abstract for still.